Reppin' : Pacific Islander youth and native justice - Camacho, Keith L. (University of Washington Press, 2021)
"From hip-hop artists in the Marshall Islands to innovative multimedia producers in Vanuatu to racial justice writers in Utah, Pacific Islander youth are using radical expression to transform their communities. Exploring multiple perspectives about Pacific Islander youth cultures in such locations as Aotearoa New Zealand, Australia, Hawai'i, and Tonga, this cross-disciplinary volume foregrounds social justice methodologies and programs that confront the ongoing legacies of colonization, incarceration, and militarization. The ten essays in this collection also highlight the ways in which youth across Oceania and the diaspora have embraced digital technologies to communicate across national boundaries, mobilize sites of political resistance, and remix popular media. By centering Indigenous peoples' creativity and self-determination, Reppin' vividly illuminates the dynamic power of Pacific Islander youth to reshape the present and future of settler cities and other urban spaces in Oceania and beyond"--